Obligation-based bribes in Vietnam: a view from the norm of reciprocity - Nguyen Thang V. (Crime, law and social change, 2022)
Studies of bribery have been heavily influenced by the cost/benefit calculation, leaving social relationship of the involved parties under-explored. We propose the norm of reciprocity as a complement theoretical lens to explain bribery exchanges and explore different types of obligation that induce bribery. Based on qualitative data from a sample of government officials in Vietnam, we found that many bribery exchanges are governed by the norm of reciprocity, i.e., obligation-based bribery. In these obligation-based bribery exchanges, the parties extend and return illegal favors based on their senses of obligation to each other, in adjacent to cost/benefit calculation. We also uncovered two types of obligation, including pragmatic and moral, and found that these types of obligation are developed through different practices. Failure to address this social element of bribery would hinder much of anti-corruption effort. The study suggests that interactions between the norm of reciprocity and wider ethical norms in governing bribery should be further addressed by both researchers and practitioners.